CircPUM1 promotes hepatocellular carcinoma progression through the miR‐1208/MAP3K2 axis. Issue 1 (15th December 2020) - Zhang, Yaqiong; Wang, Dongguo; Zhu, Tao; Yu, Jin; Wu, Xiaoyu; Lin, Weidong; Zhu, Minqi; Dai, Yingjie; Zhu, Jie
Abstract: Hepatocellular carcinoma (HCC) is a common disease with a significant mortality, and there is no effective treatment for advanced patients. Growing evidence indicates that circRNAs are closely related to HCC progression, may be used as biomarkers and targets for the diagnosis and treatment of HCC. Recent researches have shown that circPUM1 may play an oncogene role in a variety of human cancers, but its role in HCC development has not been reported. Our study found that circPUM1 could promote the proliferation, migration and invasion of HCC cells in vitro. In addition, in vivo studies showed that circPUM1 could increase the development of HCC tumours and regulate the expression of EMT‐related proteins. Furthermore, we demonstrated that circPUM1 could promote the development of HCC by up‐regulating the expression of MAP3K2 via sponging miR‐1208. Our study suggested that circPUM1 may be a potential therapeutic target for HCC.